Computer Games and Their Impact on Creativity of Primary Level Students in Tehran - Mokhtari, Tahereh (2016)
Creativity is about being sensitive to dilemmas, losses, problems, and existing errors, making propositions about and examining such issues, which finally leads to innovative findings. On the other hand, it seems that games are important in this process; since they can improve creativity of the individuals. Thus, this research pays attention to the question that whether computer games affect creativity of students at primary level in schools or not? Moreover, in this study, students of 3 main districts of Tehran municipality were studied. Based on the available data of the ministry, there were 51740 students studying in these three districts. Thus, 381 students were randomly selected as the research sample. Findings revealed that all computer games, i.e. puzzle, intellectual, and enigma, affect creativity of students at primary level in schools to different extents.